AI in semi-automated journalism: a review of Indonesia’s journalistic ethics - Besman, Abie; Evita, Nona (Jurnal Studi Komunikasi, 2024)
In the past five years, Artificial Intelligence (AI) has entered Indonesian newsrooms, aligning with the rise of Industry 4.0. This integration is poised to redefine the roles of journalists and media professionals in the future. Semi-automated journalism, a blend of human journalistic practices and AI technology, is being used in newsrooms to create news content. However, it faces challenges such as accuracy, ethics, and concerns about bias. This article uses a comprehensive literature review, covering academic publications and industry reports from the past five years, to examine semi-automated journalism in the AI era, with a focus on journalistic ethics. The review includes sources selected based on relevance, credibility, and contribution to the topic. The findings identify specific challenges such as the need for transparency in AI processes, potential biases in algorithmic decision-making, and the impact on journalistic integrity. While AI can improve efficiency, it falls short in content quality. It is crucial to train journalists for responsible AI use. Ethical principles should guide AI use in journalism to ensure the provision of quality and valuable information.